E-santé et crise sanitaire : les dispositifs de téléconsultations - Marie Berthoud (Communiquer)
Over the last fifteen years, digital tools have been developed in the health sector. This is the case with teleconsultations, or remote consultations. The exceptional context of the health crisis invites us to re-examine the issues raised by these devices from a new perspective, by considering the unprecedented context as a potential factor transforming the medical practices and uses of teleconsultations. The objective of this article is thus to answer the following question: What is the place of teleconsultation tools in a context of a health crisis like that of 2020?To provide an answer, we rely on the testimonies of doctors we collected during an investigation conducted beginning in March 2020 and during the period of the first confinement in France. Our particular interest in conducting this study was doctors’ discourses about as well as their uses of teleconsultation tools.The crisis in the healthcare system on the one hand and the health crisis on the other hand have led public health policy makers to develop the use of new telemedicine tools. This context also forced physicians themselves to adapt their professional practices. Teleconsultations provided a way for these doctors to manage a crisis situation and to address deficiencies in the healthcare system. But the devices, innovative as they are, are not hermetic to the context in which they are used. Problems related to health inequalities, legislative frameworks, lack of resources in health care in fact extend beyond traditional care situations to include digital practices. The health crisis, far from breaking with these difficulties, extends them in a context of pandemic and containment. The health crisis then appears to reveal the tensions between the benefits of e-health and the risks posed by these systems.